2021
DOI: 10.1038/s41598-021-93969-0
|View full text |Cite|
|
Sign up to set email alerts
|

Cochlear SGN neurons elevate pain thresholds in response to music

Abstract: The C-tactile (CLTM) peripheral nervous system is involved in social bonding in primates and humans through its capacity to trigger the brain’s endorphin system. Since the mammalian cochlea has an unusually high density of similar neurons (type-II spiral ganglion neurons, SGNs), we hypothesise that their function may have been exploited for social bonding by co-opting head movements in response to music and other rhythmic movements of the head in social contexts. Music provides one of many cultural behavioural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
6
0
1
Order By: Relevance
“… Dunbar et al (2021) recently found further biological evidence that supports the idea that group participation in music making increases endorphins and could therefore enhance social bonding. Specifically, they theorized that nodding one's head, a common motion when listening to and engaging with music, might stimulate certain cochlear receptors that trigger the endorphin system ( Dunbar et al, 2021 ). To test their theory, they compared participant pain thresholds before and after participating in the experimental condition (nodding their head along to music) and in several control conditions.…”
Section: Survey Of the Literaturementioning
confidence: 77%
See 1 more Smart Citation
“… Dunbar et al (2021) recently found further biological evidence that supports the idea that group participation in music making increases endorphins and could therefore enhance social bonding. Specifically, they theorized that nodding one's head, a common motion when listening to and engaging with music, might stimulate certain cochlear receptors that trigger the endorphin system ( Dunbar et al, 2021 ). To test their theory, they compared participant pain thresholds before and after participating in the experimental condition (nodding their head along to music) and in several control conditions.…”
Section: Survey Of the Literaturementioning
confidence: 77%
“…They found that the children who participated in musical play were more likely to share and help spontaneously than their peers in the non-musical groups (Beck and Rieser, 2020). Dunbar et al (2021) recently found further biological evidence that supports the idea that group participation in music making increases endorphins and could therefore enhance social bonding. Specifically, they theorized that nodding one's head, a common motion when listening to and engaging with music, might stimulate certain cochlear receptors that trigger the endorphin system (Dunbar et al, 2021).…”
Section: Social Bonding Hypothesismentioning
confidence: 88%
“…In the bonding context, the synchrony of dancing may play a role (Tarr et al, 2015), but the present results suggest that it is not necessarily more important than the physical activity itself. Indeed, Dunbar, Pearce, et al (2021) found that passive head nodding (and perhaps even foot tapping) while listening to music may be sufficient to trigger the endorphin system, and may hence induce bonding if performed in company.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian pada 1096 lansia di Jepang didapatkan lansia lebih banyak sikap negatif terhadap kaum muda dan kepuasan hidup yang lebih rendah, dan cenderung depresi (Shimizu et al, 2022). Sistem saraf tepi terlibat dalam ikatan sosial manusia melalui kapasitasnya untuk memicu sistem endorphin otak (Dunbar et al, 2021).…”
Section: Pembahasan Efek Terapi Murottal Terhadap Hormon β-Endorfinunclassified